A Systematic Literature Review: Theoretical and Conceptual Frameworks of the Determinants of Green Purchase Intention - Ekananda, Linda Wahyu; Sunarti, Sunarti; Perwangsa Nuralam, Inggang (FIA UB, 2026)
The global environmental crisis demands a transformation of people’s consumption patterns toward sustainability. This study synthesizes the theoretical frameworks and determinants of green purchase intention through a Systematic Literature Review (SLR). This study uses the PRISMA protocol to analyze 40 quantitative articles from Scopus between 2015 and 2025. The study’s findings confirm that the Theory of Planned Behavior (TPB) is the most dominant theoretical framework, used both independently and in combination with other theories such as Social Identity Theory and Signalling Theory. The main driving factors of green purchase intention include personal dimensions (attitude, perceived behavioral control, awareness, and environmental knowledge), social dimensions (subjective norms, social media, and cultural values) and marketing dimensions (the green marketing mix). Meanwhile, inhibiting factors include consumer scepticism, price sensitivity, greenwashing practices and limited product accessibility. The theoretical contribution of this study is the creation of a conceptual framework of the determinants of green purchase intention. Meanwhile, its practical contribution guides companies in creating transparent marketing strategies and in cross-sector collaboration to build a sustainable consumption ecosystem.